Peningkatan Literasi Teknologi Sistem Tertanam dan Internet of Things untuk Aplikasi Kendali Cerdas pada Mahasiswa (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
In the modern era, embedded systems and the Internet of Things (IoT) are experiencing rapid and continuous development, with their usage projected to match or even exceed the number of IoT devices globally. This technological transformation has influenced various sectors, including education, which must adapt to current digital advancements. Therefore, it is important for educational institutions to integrate embedded systems and IoT concepts into their curricula to ensure that learning remains relevant to industrial and technological demands. Improving the competence and technological literacy of students and lecturers in the fields of embedded systems and IoT, particularly for smart control applications, is expected to strengthen academic capabilities and practical skills. Through this development, higher education institutions can encourage innovation and the application of technology-based solutions in solving real-world problems. Furthermore, this effort supports the implementation of the Tri Dharma of Higher Education, especially in the areas of education and research, by promoting applied research projects and collaborative learning activities based on embedded systems and IoT technologies.